2015
DOI: 10.1101/cshperspect.a019323
|View full text |Cite
|
Sign up to set email alerts
|

RNAi and Heterochromatin Assembly

Abstract: SUMMARYThe involvement of RNA interference (RNAi) in heterochromatin formation has become clear largely through studies in the fission yeast Schizosaccharomyces pombe and plants like Arabidopsis thaliana. This article discusses how heterochromatic small interfering RNAs are produced and how the RNAi machinery participates in the formation and function of heterochromatin.Outline

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
283
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 270 publications
(285 citation statements)
references
References 123 publications
(155 reference statements)
2
283
0
Order By: Relevance
“…Silent chromatin domains of Saccharomyces cerevisiae are epigenetically inherited and exhibit variegated expression under certain circumstances. In contrast to heterochromatin in Schizosaccharomyces pombe and higher eukaryotes, budding yeast silent chromatin lacks a number of hallmark characteristics including methylation of histones, heterochromatin protein 1 (HP1), and the participation of RNA interference (RNAi) (Martienssen and Moazed 2015). In essence, S. cerevisiae silent chromatin is a stripped-down version of heterochromatin found in other organisms.…”
mentioning
confidence: 99%
“…Silent chromatin domains of Saccharomyces cerevisiae are epigenetically inherited and exhibit variegated expression under certain circumstances. In contrast to heterochromatin in Schizosaccharomyces pombe and higher eukaryotes, budding yeast silent chromatin lacks a number of hallmark characteristics including methylation of histones, heterochromatin protein 1 (HP1), and the participation of RNA interference (RNAi) (Martienssen and Moazed 2015). In essence, S. cerevisiae silent chromatin is a stripped-down version of heterochromatin found in other organisms.…”
mentioning
confidence: 99%
“…To amplify small RNAs, RITS recruits the RNA-dependent RNA Polymerase complex (RDRC), which synthesizes doublestranded RNA that is processed by Dicer into siRNAs. In addition, RITS recruits the H3K9 methyltransferase complex CLRC to chromatin, which leads to repressive histone 3 lysine 9 methylation (H3K9me), recruitment of HP1 proteins, and heterochromatin formation (Volpe et al 2002;Verdel et al 2004;Allshire and Ekwall 2015;Holoch and Moazed 2015;Martienssen and Moazed 2015;Zocco et al 2016).…”
mentioning
confidence: 99%
“…However, as with repeat density, piRNA sequence density by itself is also an insufficient predictor of transgene phenotypes ( Figure 6; Table S4), indicating that multiple conditions have to be met for stable heterochromatin to form, possibly including low levels of transcription coming from the transgene locus at the correct developmental time, when heterochromatin is being established. A model that depends on some transcription to achieve silencing, apparently by generating a transcript, which can hybridize with the available piRNAs to initiate silencing events, is well established in the yeast Schizosaccharomyces pombe (Martienssen and Moazed 2015). Mapping the insertion sites of variegating reporters recovered in our screen revealed that for both the P{T1} and the P{T4} transgenes the majority of the insertion sites are in regions of the genome previously described as supporting heterochromatin formation and PEV.…”
Section: Discussionmentioning
confidence: 97%